A Method for Quantification of Stretch Reflex Excitability During Ballistic Reaching - Thomas A. M. Plaisier; Ana Maria Acosta; Julius P. A. Dewald (IEEE, 2023)
Stretch reflexes are crucial for performing accurate movements and providing rapid corrections for unpredictable perturbations. Stretch reflexes are modulated by supraspinal structures via corticofugal pathways. Neural activity in these structures is difficult to observe directly, but the characterization of reflex excitability during volitional movement can be used to study how these structures modulate reflexes and how neurological injuries impact this control, such as in spasticity after stroke. We have developed a novel protocol to quantify stretch reflex excitability during ballistic reaching. This novel method was implemented using a custom haptic device (NACT-3D) capable of applying high-velocity (270 °/s) joint perturbations in the plane of the arm while participants performed 3D reaching tasks in a large workspace. We assessed the protocol on four participants with chronic hemiparetic stroke and two control participants. Participants reached ballistically from a near to a far target, with elbow extension perturbations applied in random catch trials. Perturbations were applied before movement, during the early phase of movement, or near peak movement velocity. Preliminary results show that stretch reflexes were elicited in the stroke group in the biceps muscle during reaching, as measured by electromyographic (EMG) activity both before (pre-motion phase) and during (early motion phase) movement. Reflexive EMG was also seen in the anterior deltoid and pectoralis major in the pre-motion phase. In the control group, no reflexive EMG was seen, as expected. This newly developed methodology allows the study of stretch reflex modulation in new ways by combining multijoint movements with haptic environments and high-velocity perturbations.